The Gambia : Second Review Under the Extended Credit Facility Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The Gambia is experiencing a second wave of COVID-19 cases. The vaccination campaign started in early March 2021, but the pace is slow, due to vaccine availability and hesitancy. Presidential and parliamentary elections are planned for December 2021 and April 2022, respectively.